Penerapan Keadilan Restoratif Dalam Penyelesaian Kasus Kecelakaan Lalu Lintas Yang Mengakibatkan Matinya Orang - Sempaty Yehuda Tasane; Juanrico Alfaromona Sumarezs Titahelu; Lionie Lokollo (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Penyelesaian perkara pidana melalui keadilan restoratif pada tahap penyidikan dikirimkan ke Jaksa Penuntut Umum dan penerapannya terhadap semua tindak pidana yang tidak menimbulkan korban manusia sehingga menimbulkan masalah dalam penerapannya.Purposes of the Research: This research is a normative-empirical juridical research using a statutory approach and a case approach.Methods of the Research: Primary data collection techniques through field research and library research to obtain secondary data.Results of the Research: The results of the study that the application of restorative justice in the settlement of traffic accident cases, the Center was carried out by the Investigator after there was peace between the perpetrator and the victim's family which was carried out after the Investigator sent a Notice of the Commencement of the Investigation to the Public Prosecutor so that the handling of the case was not continued. The factors that influence the application of restorative justice in the settlement of traffic accident cases consist of law enforcement factors, namely the investigator's knowledge and understanding of the applicable laws and regulations, the legal substance factor, namely the substance of the Circular Letter of the Chief of Police which regulates material requirements that do not accommodate the settlement of cases. with human victims and formal requirements regarding the period of time in the application of restorative justice only to criminal acts at the investigation stage before sending the Notification of the Commencement of Investigation, and community legal cultural factors related to values, attitudes and behavior in people's lives so that they influence decision making to settle accident cases. The traffic it experiences through restorative justice.